Perceived Family Burden Between Caregivers of Schizophrenic Patients - Nayak, Mihir Ranjan; Mallik, Tapasa; Hembram, Sarathi; Dash, Manaswini (Jurnal EMT KITA, 2019)
The purpose of this study was to assess and examine the family burden among male and female nurses with schizophrenia patients. The sample population consisted of 60 male and female caregivers of schizophrenic patients selected using purposive sampling from outside patients and indoor patients, MHI, COE, SCBMCH, Cuttack. Odisha. The Family Expense Interview Schedule is applied to caregivers. The results showed that female caregivers had more family burden in all domains compared to male caregivers of schizophrenic patients.Â Keywords: Family Burden, Caregivers, Schizophrenia.